User Interface Information System for Using Account Services (Joint Account) WEB-Based - Indah Purnama Sari; Ismail Hanif Batubara (CERED Indonesia Institute, 2021)
Rekber Services (Joint Account) is a method of payment or transactions made online. This method is considered safer than having to transfer directly to the seller's account. Abroad, the account is known as Escrow Service. Not only abroad, the Indonesian banking world is also known as ES (Escrow Service).